Reproductive Biology of Horseshoe Crab (Carcinoscorplus Rotundicaude) with Emphasis on Gonad and Gamete Morphology - Hajeb, Parvaneh (2005)
Samples of adult Carcinoscorpius rotundicauda caught from Pulau Lumut, Selangor, from November 2003 to February 2005 were conditioned in the Hatchery Unit, Universiti Putra Malaysia and used for all the experiments. C. rotundicauda was identified based on its morphological characteristics and at the same time age determination was carried out. It is the smallest of four extant species of horseshoe crabs. Male adults were smaller than females. Based on the size estimation, it was found that 75% of collected C. rotundicauda males were of 10 to 11 years old (after 14'~m olt), while 59% of the females were 1 1 to 12 years old (after 1 5th molt). The male reproductive organ was investigated morphologically and histologically. It consisted of testis and spermiducts network which was filled with spermatogenic cells (spermatogonia, primary and secondary spermatocytes) that lied along the basement membrane with spermatozoa close to the testicular lumen. SEM observations showed that a mature spermatozoa consisted of a head with a cap-like acrosomal vesicle, midpiece and a long flagellum. The average size of the sperm head was 4.6 pm while the flagellum was 33 pm in length. The acrosomal filament formed 11 helical coils around the nucleus. Observation on the cross-section of the flagellum showed a 9+0 axoneme pattern without the central tubules. Morphology and histology of mature ovary and egg were studied. The female gonad was located in the prosomal part, consisted of ovarian tubes and oviducts which opened as a pair of gonopores on the ventral side of the opisthosoma. A C. rotundicauda egg (of 2.25 to 2.58 mm in diameter) had a large yolk covered with an elastic chorion with two layers, the outer basement lamina (3.03 pm thickness) and the inner vitelline envelope (43.6 pm thickness). Fecundity of C. rotundicauda ranged from 993 to 7937 eggs per adult, increasing with body size and weight. Interactions between egg and sperm were observed under SEM. Spermatozoa were attached to the outer layer of the egg's chorion. In this study, high sperm concentration (23 - 30 x lo6 spermlml) resulted in numerous sperms attached to the egg surface. Even though many sperms can attach to the egg surface and pass through the egg's envelope, only one will transfer its nucleus into the vitellus and fertilize the egg.